Extending Research on Deception in Sport – Combining Perception and Kinematic Approaches - Panten, Josefine; Loffing, Florian; Baker, Joseph; Schorer, Jörg (Frontiers in Psychology, 2019)
The high spatio-temporal demands in antagonistic sport contexts require a strategic interplay between anticipation from early kinematic cues and the possibility of deceptive movement strategies. Despite the importance of the interaction between observer and deceiver, this dyad is usually considered separately in perceptual-cognitive and kinematic perspectives. The present approach proposes a consolidation of perceptual-cognitive and kinematic perspectives into a dyad of deception that focuses on the interplay between opposing actors within their respective antagonistic contexts. For analyzing movement deception within the dyad, a framework is proposed. Applying a functional approach, the deceptive act is regarded as the means of solving a performance task with high spatio-temporal demands in an antagonistic context. The framework involves three elements: First, the context of the movement deception is evaluated relative to the constraints imposed by the athlete, object and deceptive content. Together these constraints generate a range of potential kinematic options for movement deception. Successful deception is bound to correspond to that range of functionality. Second, movement deception is further determined by the spatio-temporal constraints of the original context. More simply, misleading information is only useful if it mimics elements of the genuine movement. Third, the dyadic aspect emphasizes targeting the spatio-temporal interplay as well as differentiating between active movement deception and co(ntra)-active deception by indirectly shaping an outcome on the basis of inadvertent informational exchange. Our goal with this framework is to supplement movement deception research by providing a conceptional context that can be applied across sports.